A systematic review to inform the development of a Canadian caries risk assessment tool for use by primary healthcare providers. Issue 6 (17th February 2021) - Schroth, Robert J.; Rothney, Janet; Sturym, Melina; Dabiri, Darya; Dabiri, Donya; Dong, Cecilia C.; Grant, Cameron G.; Kennedy, Tara; Sihra, Rena
Abstract: Background: Caries risk assessment (CRA) tools may assist in identifying children at risk of early childhood caries. Aim: To complete a systematic review of CRA and develop a Canadian CRA tool for preschool children for use in non‐dental clinical settings. Design: Systematic searches of relevant databases were conducted. Potential variables were based on strength of associations (odd ratios, relative risk, hazard ratios, etc), frequency of occurrence, and existing CRA tools. Quality of the evidence assessments were performed by at least two review teams through consensus following GRADE. Results: Overall, 25 publications met the inclusion criteria, all prospective in design. Based on this review, variables to be considered when developing a new CRA tool for use with preschool children are as follows: age, socioeconomic status, family toothbrushing habits, fluoride exposure, infant feeding practices, dietary habits/behaviours, dental home, caries experience, visible plaque, and enamel defects. The environmental scan identified 22 CRA tools suggesting other additional variables to consider including in a CRA tool, including special healthcare needs, enamel defects, and dental attendance. Conclusions: This review informed the development of a Canadian CRA tool for use by primary healthcare professionals, which may improve access to oral health assessments and increase interprofessional collaboration.